Seismic Damage Quantification of RC Short Columns from Crack Images Using the Enhanced U-Net - Zixiao Chen; Qian Chen; Zexu Dai; Chenghao Song; Xiaobin Hu (Buildings)
It is of great importance to quantify the seismic damage of reinforced concrete (RC) short columns since they often experience severe damage due to likely excessive shear deformation. In this paper, the seismic damage quantification method of RC short columns under earthquakes is proposed based on crack images and the enhanced U-Net. To this end, RC short-column specimens were prepared and tested under cyclic loading. The force-displacement hysteresis curves were obtained to quantitatively calculate the damage indicator of the RC short column based on the energy criterion. At the same time, crack images of the column surfaces were taken by smartphones using the partition photographing scheme and image stitching algorithm. The widely used U-Net was enhanced by adding a double attention mechanism to segment the cracks in the images. The results demonstrate that it has better accuracy in terms of recognizing tiny cracks compared to the original U-Net. By image analysis, the crack information was further extracted from the crack images to investigate the damage development of RC short columns. Finally, correlations between the damage indicator based on the energy criterion and crack information of the RC short columns under cyclic loading were analyzed, showing that the highest correlation exists between the damage indicator and the total crack area. Finally, the normalized total crack area, i.e., the ratio between the total crack area and the corresponding monitored area of the surface, is defined to quantify the seismic damage of RC short columns when utilizing crack images for damage assessment.